Development of Chameleon Surface - Kim, You-suk; Kim, Jin-yung; Hong, Sung-dae (International Journal of Engineering and Technology, 2018)
Background/Objectives: This study is about the development of chameleon surface which combines a dynamic surface with a pin-screen method and a surface projection mapping. It aims to show a higher immersion experience to the audience through physical display and projection mapping. Methods/Statistical analysis: Due to advanced design methods and materials, we have developed a telescopic linear actuator, which is a faster, longer and lighter motion control module. We also studied material and fabric combination techniques for stretchable screens on each actuator module for projection mapping and projection mapping technology for projecting curved surfaces with multiple projectors. Findings: The telescopic actuator has a speed of more than 1.7m/s, a travel distance of more than 1m, and weighs about 3 4kg, which is about 25% more than that of the past. Also, the stretchable screen using composite material has elastic recovery rate of 96% and maximum elongation of 180% is achieved. In the aspect of projection mapping projected on a dynamic surface, the overlapping area resulting from multiple projections is solved using 3D edge blending. This achieves an error range of 6.43 mm when projecting onto surface, maintains a speed of 24 fps or higher. Improvements/Applications: The Chameleon surface is expected to be utilized in outdoor advertising, stage equipment, and kinetic art, and is expected to be used as a next-generation physical display after researching and optimizing the contents in the future. Â Â